Alexander Davidson, Two Models of Welfare: The Origins and Development of the Welfare State in Sweden and New Zealand, 1888-1988, Uppsala: Acta Universitatis Uppsaliensis, 1989, 432 s., SEK. 198,00. - Schwartz, Herman (Politica, 1990)
-